Morphological integration affects the evolution of midline cranial base, lateral basicranium, and face across primates. Issue 1 (9th July 2019) - Neaux, Dimitri; Wroe, Stephen; Ledogar, Justin A.; Heins Ledogar, Sarah; Sansalone, Gabriele
Abstract: Objectives: The basicranium and face are two integrated bony structures displaying great morphological diversity across primates. Previous studies in hominids determined that the basicranium is composed of two independent modules: the midline basicranium, mostly influenced by brain size, and the lateral basicranium, predominantly associated with facial shape. To better assess how morphological integration impacts the evolution of primate cranial shape diversity, we test to determine whether the relationships found in hominids are retained across the order. Materials and methods: Three‐dimensional landmarks (29) were placed on 143 computed tomography scans of six major clades of extant primate crania. We assessed the covariation between midline basicranium, lateral basicranium, face, and endocranial volume using phylogenetically informed partial least squares analyses and phylogenetic generalized least squares models. Results: We found significant integration between lateral basicranium and face and between midline basicranium and face. We also described a significant correlation between midline basicranium and endocranial volume but not between lateral basicranium and endocranial volume. Discussion: Our findings demonstrate a significant and pervasive integration in the craniofacial structures across primates, differing from previous results in hominids. The uniqueness of module organization in hominids may explain this distinction. We found that endocranial volume is significantly integrated to the midline basicranium but not to the lateral basicranium. This finding underlines the significant effect of brain size on the shape of the midline structures of the cranial base in primates. With the covariations linking the studied features defined here, we suggest that future studies should focus on determining the causal links between them.